Guidelines of the Brazilian Society of Rheumatology for the treatment of systemic autoimmune myopathies - Fernando Henrique Carlos de Souza (Advances in Rheumatology, 2019)
Abstract Background Recommendations of the Myopathy Committee of the Brazilian Society of Rheumatology for the management and therapy of systemic autoimmune myopathies (SAM). Main body The review of the literature was done in the search for the Medline (PubMed), Embase and Cochrane databases including studies published until June 2018. The Prisma was used for the systematic review and the articles were evaluated according to the levels of Oxford evidence. Ten recommendations were developed addressing the management and therapy of systemic autoimmune myopathies. Conclusions Robust data to guide the therapeutic process are scarce. Although not proven effective in controlled clinical trials, glucocorticoid represents first-line drugs in the treatment of SAM. Intravenous immunoglobulin is considered in induction for refractory cases of SAM or when immunosuppressive drugs are contra-indicated. Consideration should be given to the early introduction of immunosuppressive drugs. There is no specific period determined for the suspension of glucocorticoid and immunosuppressive drugs when individually evaluating patients with SAM. A key component for treatment in an early rehabilitation program is the inclusion of strength-building and aerobic exercises, in addition to a rigorous evaluation of these activities for remission of disease and the education of the patient and his/her caregivers.